Herbal Medicines In Forensic Toxicology: Current Evidence, Analytical Challenges, And Future Perspectives: Herbal Medicines In Forensic Toxicology: Current Evidence, Analytical Challenges, And Future Perspectives - Ricka Brillianty Zaluchu; Nurul Qamariah (Jurnal Surya Medika (JSM), 2026)
The increasing global use of herbal medicines has expanded their relevance in forensic toxicology, particularly in cases involving accidental poisoning, intentional intoxication, herb–drug interactions, organ toxicity, product adulteration, and unexplained death. Although botanical products are commonly perceived as safe, many contain potent bioactive compounds capable of producing severe neurological, hepatic, cardiovascular, and renal toxicity. Their forensic investigation is complicated by complex phytochemical compositions, variable product quality, limited toxicological reference data, and the frequent presence of undeclared pharmaceuticals or contaminants. This narrative review summarizes the forensic significance of herbal medicines, major toxicological mechanisms, relevant biological specimens, current analytical techniques, interpretative challenges, and medico-legal implications. Particular attention is given to toxicologically important plants such as Mitragyna speciosa, Aconitum spp., Datura stramonium, Nerium oleander, Cerbera odollam, and Aristolochia spp. The review also examines the application of liquid chromatography–tandem mass spectrometry, gas chromatography–mass spectrometry, high-resolution mass spectrometry, spectroscopic methods, DNA-based identification, metabolomics, chemical fingerprinting, and artificial intelligence in the detection and authentication of herbal constituents. Current evidence indicates that the detection of a phytochemical confirms exposure but does not independently establish causation. Reliable forensic interpretation requires integration of toxicological findings with product analysis, botanical authentication, autopsy and histopathological observations, exposure history, and scene evidence. Major limitations include incomplete toxicological databases, scarce certified reference standards, postmortem redistribution, and the absence of validated toxic and lethal concentration ranges for most herbal compounds. Future progress will depend on standardized analytical protocols, expanded international databases, and stronger interdisciplinary collaboration to improve medico-legal decision-making and public health protection